Correlation of Incident Potentially Inappropriate Medication Prescriptions and Hospitalization: An Analysis Based on the PRISCUS List - Henschel, Frank (Drugs Real World Outcomes, 2015)
BACKGROUND: Multimorbidity and polypharmacy represent a major problem for elderly patients. Potentially inappropriate medication (PIM) use is highly prevalent among the elderly. PIMs are considered high-risk drugs and are suspected to be responsible for adverse drug events (ADEs) leading to hospitalization. OBJECTIVE: The objective of this study was to determine hospitalization rates related to selected ADEs in elderly patients with an incident prescription of a PIM as defined by the PRISCUS list. A second objective was to identify other factors independently associated with hospitalization. METHODS: We retrospectively analysed a full census of pharmaceutical claims, from one of the largest public sickness funds in Germany, for 647,073 patients aged ≥65 years in 2010, the year of publication of the PRISCUS list. Patients who received an incident PIM in 2010 were assigned to the intervention group. Propensity score matching was used to build a control group of patients at a comparable risk level who received an incident equivalent non-PIM. The risk of hospitalization due to PIM prescription was estimated via the odds ratio (OR). Risk factors were analysed via logistic regression models. RESULTS: The results showed significantly more ADEs in the PIM group. The OR for hospitalization was 1.54 [95 % confidence interval (CI) 1.23–1.93] for patients receiving any PIM compared with those who received a non-PIM. This trend remained stable [OR 1.46 (95 % CI 1.16–1.84)] after adjustment for relevant covariates in the logistic regression models showing ORs for each risk factor. Besides PIMs, common risk factors such as greater age, comorbidity and specific drug classes were significantly responsible for hospitalization. CONCLUSION: PIMs (as defined by the PRISCUS list) are associated with high rates of ADEs associated with hospitalization. Our study suggests that PIM reduction may result in a lower risk of hospitalization in the elderly.